LIMITATIONS AND DEFICIENCIES OF PHARMACO-ECONOMIC STUDIES IN THE RUSSIAN FEDERATION COMMENTS TO THE ARTICLE OF S. L. PLAVINSKIY ET AL. «PHARMACOECONOMIC ANALYSIS OF THE IMPACT ON THE BUDGET COSTS OF ADDING DEXMEDETOMIDINE (DEXDOR) INTO THE LIST OF VITAL AND ESSENTIAL DRUGS» - D. N. Protsenko (Вестник анестезиологии и реаниматологии)
.